Cryptogams of the Parque Estadual das Fontes do Ipiranga, São Paulo, SP. Algae, 46: Bacillariophyceae (Bacillariaceae) - Lehmkuhl, Elton Augusto (2021)
Survey was carried out of family Bacillariaceae (Bacillariophyceae) in the Parque Estadual das Fontes do Ipiranga, São Paulo, southeast Brazil, based on 28 samples. Analysis of specimens from the morphological point of view was made utilizing light microscope after oxidation and preparation of permanent slides. Four genera, 27 species and three varieties that are not the typical of their respective species were identified, from which nine are new registers for the State São Paulo [Nitzschia acicularis Hustedt, N. acidoclinata Lange-Bertalot, N. clausii Hantzsch, N. dissipata (Kützing) Rabenhorst, N. intermedia Hantzsch, N. palea (Kützing) W. Smith var. tenuirostris Grunow, N. subacicularis Hustedt, Tryblionella debilis Arnott ex O’Meara, and T. victoriae Grunow], and two are new records for the Brazilian territory [Grunowia solgensis (Cleve-Euler) Aboal and N. dissipata (Kützing) Rabenhorst var. borneensis Kützing]. Each identification was based on population samples, is presented by their morphological description and measurements, and is illustrated by photomicrographs.